Functional diversity and primary production predict future patterns of periphyton productivity after species extinction - Dunck, Bárbara (2022)
Understanding of the trait-based ecology of the periphytic algal community has increased in the last decade. However, the relationship between their functional diversity and ecosystem functions, such as primary production, has been speculated on, but yet not proven. Human impacts promote changes in biotic communities leading to a risk of extinction, with consequences for the functioning of aquatic ecosystems. In this study, we unraveled the associations between the taxonomic and functional components of periphytic algal diversity, stream eutrophication, and productivity patterns. Furthermore, we simulated future patterns of species extinction to predict how productivity may change when facing extinction. Primary production and taxonomic and functional diversity of the periphytic algal communities were estimated in five streams across a trophic gradient in the Ave River basin (northwest Portugal). Our results demonstrated that eutrophication led to a unimodal pattern of taxonomic diversity, while functional diversity tended to increase with increasing eutrophication. We found that only functional diversity had a positive association with primary production. The extinction estimations indicated that almost all species found in our study were at high extinction risk. When we spatially scaled our extinction simulations, we found poor-productive streams after the extirpation of a few species. However, at the regional scale, the ecosystem supports the extinction of at least 40% of species before turning into a poor-productive system. Intermediate levels of disturbance are probably beneficial for the diversity of periphytic algal communities, to a certain extent. Moreover, functionally diverse communities were more productive, and the alleged future extinction of species is likely to lead to poor-productive streams if regionally focused conservation initiatives are not implemented. We recommend that, using simulations of functional extinction, it is possible to infer how the loss of these microorganisms could alter ecosystem functioning, to better predict human impacts on aquatic ecosystems.